Patterns of streamflow regimes along the river network: The case of the Thur river. (July 2017) - Doulatyari, Behnam; Betterle, Andrea; Radny, Dirk; Celegon, Elisa Alessi; Fanton, Pietro; Schirmer, Mario; Botter, Gianluca
Abstract: A modeling framework for point-wise prediction of the probability density function and flow duration curve of streamflows along complex river networks is presented. The predictions are based on catchment-scale climatic and morphological features, without calibration on observed discharge time-series. The framework was applied to a test basin in north-eastern Switzerland, and relevant flow statistics were validated at six sub-catchment outlets with satisfactory results. Spatial patterns of flow regime exhibit a strong climatic signature, mostly driven by reduced rainfall depths and increasing effective rainfall frequency in the downstream areas. The increasing non-linearity of the catchment response with contributing area is reflected by the observed increase in the recession parameters along the main river channel. This framework offers a novel approach for assessing the spatial patterns of streamflows based on limited information, which is important for evaluation of human and ecological functions in riverine systems. Highlights: Process based framework for predicting basin-scale spatial variability of flow regimes. Flow regimes patterns are the by-product of climate gradients and network structure. Hydrologic response becomes more non-linear at larger spatial scales.